Rebellious Behaviors in Adolescents With Epilepsy. (30th May 2017) - Smith, Aimee W; Mara, Constance; Ollier, Shannon; Combs, Angela; Modi, Avani C
Abstract: Objectives: The study aims are to (1) examine the prevalence of risk-taking (i.e., behaviors that can be categorized as rebellious or reckless) and (2) determine the influence of risk-taking on adherence, seizures, and health-related quality of life (HRQOL) in adolescents with epilepsy. An exploratory aim was to identify predictors of risk-taking. Methods: Fifty-four adolescents with epilepsy ( M  = 15.33 ± 1.46 years) and caregivers completed questionnaires on demographics, risk-taking, parent–child relations, adolescent inattention/hyperactivity, and HRQOL at four time points across 1 year. Seizure occurrence and electronically monitored adherence were also collected. Results: Rebellious behaviors were normative and stable over 1 year in adolescents with epilepsy. Higher rebelliousness was related to poorer adolescent-reported memory HRQOL. The only significant positive predictor of rebellious behaviors was adolescent age. Conclusions: Adolescents with epilepsy endorsed normative levels of rebelliousness, which is negatively related to HRQOL. Older adolescents may warrant clinical attention.